Mycobacterium avium Complex Osteomyelitis in Persons With Human Immunodeficiency Virus: Case Series and Literature Review. (15th June 2015) - Wood, Brian R.; Buitrago, Martha O.; Patel, Sugat; Hachey, David H.; Haneuse, Sebastien; Harrington, Robert D.
Abstract: In persons with advanced immunosuppression, Mycobacterium avium complex (MAC) typically causes disseminated disease with systemic symptoms. We report 2 cases in which MAC caused localized osteomyelitis in human immunodeficiency virus (HIV)-infected individuals on antiretroviral therapy with rising CD4 counts. We summarize 17 additional cases of HIV-associated MAC osteomyelitis from the literature and compare CD4 count at presentation for vertebral cases versus nonvertebral cases, which reveals a significantly higher CD4 at presentation for vertebral cases (median 251 cells/µL vs 50 cells/µL; P = .043; Mann–Whitney U test). The literature review demonstrates that the majority of cases of MAC osteomyelitis, especially vertebral, occurs in individuals with CD4 counts that have increased to above 100 cells/µL on antiretroviral therapy. Among HIV-infected individuals with osteomyelitis, MAC should be considered a possible etiology, particularly in the setting of immune reconstitution.